Mechanical performance of roller compacted rubbercrete with different mineral filler - Adamu, M. (Penerbit UTM Press, 2017)
The rate of waste tire generation globally continues to escalate due to increase in vehicle usage. Scrap tires continue to pose serious environmental, health and aesthetic problems. Due limitation in the recycling of scrap tires, one of the most viable solution is to used crumb rubber from scrap tire as partial replacement to fine aggregate in concrete industry. This is rationalized as the production of concrete hit more than 3.8 billion cubic meters annually, therefore, it could provide a solution on conservation of natural aggregate and as well as improve properties of concrete. However, the major setback in the use of crumb rubber in concrete is loss in strength. In this paper, crumb rubber was used to partially replaced fine aggregate at 0, 10, 20 and 30 by volume in roller compacted concrete for pavement applications to produce roller compacted rubbercrete (RCR) to improve its flexural strength and ductility. Several trials were done to achieve the combined grading as recommended by ACI 211.3R, and finally a combination of 55 fine aggregate, 40 coarse aggregate and 5 fine sand as mineral filler was used. In order to mitigate the effect of strength loss, silica fume and fly ash were used to replace natural fine sand as mineral fillers. The Results showed that fresh density, compressive, splitting and flexural strengths decreases with increase in partial replacement of fine aggregate with crumb rubber. However using silica fume as a mineral filler was successful in mitigating loss in compressive, tensile and flexural strengths for up to 20 crumb rubber replacement level, while fly ash as a mineral filler mitigated loss in strength for up to 10 crumb rubber compared natural fine sand mineral filler. The flexural strength was found to increase with 10 crumb rubber for all type of mineral filler. © 2017 Penerbit UTM Press. All rights reserved.